ANALISA TERMAL PADA STERILIZER CRUDE PALM OIL DI PT. PERKEBUNAN NUSANTARA V SEI GALUH - Rafil Arizona Rafil; Liberti Martua Sinaga; Shandy Kurniadi; Eddy Elfiano; Sehat Abdi Saragih (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
Boiling oil palm, especially in Fresh Fruit Bunches (TBS) is one of the most important stages in the palm oil processing process. During the boiling process, it is hoped the temperature and steam pressure, as well as the working time on the sterilizer, are correct so that they do not damage the quality of CPO and that the sterilizer material is also maintained and safe.. Therefore, a thermal analysis was carried out on a horizontal sterilizer using a thermodynamic analysis approach and looking for thermal efficiency at peaks I, II, and III. The research was completed using a mathematical analysis method. Data collection was carried out using literature study techniques and field observations. The results showed that the value of transient conduction on the lorry peak I: 392.476 MJ, peak II: 77.186 MJ, peak III: 28.457 MJ. In oil palm fruit, peak I: 2,164.273 MJ, peak II: 1,407.039 MJ, peak III: 480.314 MJ. at peak I: 606.5398 MJ, peak II: 910.7164 MJ, peak III: 1,063.0479 MJ. The final temperature of the lorry at peak I: 384.5 K, peak II: 400.5 K, peak III: 406.42 K. Meanwhile, the oil palm fruit at peak I: 350.20 K, peak II: 390.115 K, and peak III: 406.268 K. Sterilizer efficiency at peak I: 81.081%, peak II: 80.6716%, at peak III: 80.5332%.